Activating HRAS mutation in a case of inverted ductal papilloma of the salivary gland. Issue 12 (21st September 2021) - Ide, Fumio; Ito, Yumi; Kikuchi, Kentaro; Satomura, Kazuhito; Ogawa, Ikuko; Yamamoto, Hidetaka
Abstract: Inverted ductal papilloma (IDP) is one of the least common benign papillary/cystic neoplasms of the salivary duct system, being characterized histologically by florid hyperplasia of duct‐type epithelial cells into a cystic lumen near the orifice with occasional endophytic growth of the surface squamous epithelium along the terminus of the affected excretory duct. Given its rarity, the exact etiology of IDP remains to be defined. We herein present the first evidence of oncogenic HRAS mutation in a case of oral IDP. This finding, together with the frequent and specific BRAF mutations in sialadenoma papilliferum reported in the recent literature, supports an active role of the MAP‐kinase cascade in the pathogenesis of benign papillary neoplasms of terminal duct origin.